Displaced children with cancer in Lebanon: A sustained response to an unprecedented crisis. Issue 7 (28th February 2018) - Saab, Raya; Jeha, Sima; Khalifeh, Haifaa; Zahreddine, Lama; Bayram, Layal; Merabi, Zeina; Abboud, Miguel; Muwakkit, Samar; Tarek, Nidale; Rodriguez‐Galindo, Carlos; El Solh, Hassan
Abstract : BACKGROUND: The unrest in Syria has resulted in an escalating refugee crisis. The postwar lack of health care infrastructure in Iraq has also resulted in Iraqis seeking health care in neighboring countries. Pediatric cancer is largely curable, although its treatment is expensive and complex. Strategies to implement pediatric cancer care with curative intent in these vulnerable populations are lacking. METHODS: To assess the feasibility of a collaborative approach for the provision of care to displaced children with cancer, this study reviewed the experience of the authors over the past 6 years in Lebanon, the country with the highest number of refugees per capita in the world. RESULTS: The American University of Beirut Medical Center and the Children's Cancer Center of Lebanon Foundation, in partnership with St. Jude Children's Research Hospital and the American Lebanese Syrian Associated Charities, established 3 successive funding programs to treat displaced children with cancer along with a continuous assessment of resource utilization. Between 2011 and 2017, 575 non‐Lebanese children suspected to have cancer were evaluated. Of those, 311 received direct medical support, with 107 receiving full‐treatment coverage and 204 receiving limited‐workup/specialty services; the remaining 264 patients received medical consultations. CONCLUSIONS: In addition to providing lifesaving humanitarian support, the coordination of care delivery, including the establishment of guidelines for prioritization, can help direct future efforts. Many patients continue to be in dire need of support, and this should be addressed via collaboration among governmental, nongovernmental, and health care organizations. Cancer 2018;124:1464‐72 . © 2018 American Cancer Society . Abstract : Effective management of pediatric cancer care in refugee populations is possible through the use of a strategic collaborative approach to ensure the efficient use of resources for the provision of good‐quality and accountable care. Mobilization of global advocacy in both the private and public sectors is needed to ensure the sustainability of such approaches to answer the increasing needs of such vulnerable patient populations. See also pages 1322‐25.